Knowledge Management in University Administration in Malaysia - Roshayu, Mohamad; Karen, Manning; Arthur, Tatnall (2013)
Knowledge management is important to both business and government organisations as a means of improving their operations. This research project investigated cultural factors affecting knowledge management in higher education administrative departments in Malaysia. It considered strategic decisions made by university administrations and adoption decisions made by individual staff members. As the study was conducted in the South- East Asia region, organisational culture in this region is important. The paper describes the factors found to affect the practice of knowledge management in higher education in Malaysia.